The People's Republic of China : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The People's Republic of China. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights China's continued transition to sustainable growth, with progress on many fronts. Growth slowed to 6.9 percent in 2015 and is projected to moderate to 6.6 percent in 2016 owing to slower private investment and weak external demand. The economy is advancing on many dimensions of rebalancing, particularly switching from industry to services and from investment to consumption. But other aspects are lagging, such as strengthening state-owned enterprises and financial governance and containing rapid credit growth. The current account surplus is projected to decline to 2.5 percent of GDP in 2016 as imports increase and the services deficit widens with continued outbound tourism.